2014
DOI: 10.1111/pai.12187
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomic analysis identifies a role for intercellular adhesion molecule 1 in childhood asthma

Abstract: In this unique prospective study, we demonstrated that ICAM1 is associated with asthma development on DNA, mRNA, and protein level. Thus, ICAM1 is likely to be involved in the development of childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
(38 reference statements)
1
14
0
2
Order By: Relevance
“…The allele frequencies of rs5491 and rs5498 in our data were similar to the Chinese data in the HapMap project and the results of another two Chinese studies [31,32]. Both of the studied ICAM1 SNPs were functional SNPs, so they could influence the encoded enzyme [23,24,33]. …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The allele frequencies of rs5491 and rs5498 in our data were similar to the Chinese data in the HapMap project and the results of another two Chinese studies [31,32]. Both of the studied ICAM1 SNPs were functional SNPs, so they could influence the encoded enzyme [23,24,33]. …”
Section: Discussionsupporting
confidence: 86%
“…However, Li et al indicated that the risk for asthma was higher in rs5491 T allele carriers [22]. The ICAM1 rs5498 A allele had been reported to be positively associated with childhood asthma in African-Americans [22], Germans [23], and the Dutch [24]. The ICAM1 haplotype of rs5493 (G241S) and rs5498 [22], and another haplotype of rs5498 and rs885743 (in the 3’-untranslated region) [23] were reported to be associated with the risk for childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic because the majority of genomic studies do not implicitly model sex interaction effects [10, 34, 35]. Further, many two-step genome-wide approaches to test interaction assume main (marginal) effects [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, noninvasive sampling in preschool age is particularly important, using, for example, exhaled breath condensate (EBC) to detect asthma development-associated biomarkers of the infiltration type (Table 1; section infiltrate-derived biomarkers), such as IL-4, IL-8, IL-10, IL-13 and sICAM1 (56). CCL-5 significantly correlates with both reduction in FEV1 and increase in airway resistance, while increased levels of TNF-a and TGF-b significantly correlate with nonspecific bronchial hyperresponsiveness.…”
Section: Disease Progression In Childrenmentioning
confidence: 99%